The Christmas gathering [large type] - Gray, Shelley Shepard; Good, Rachel J.; Worth, Lenora (Center Point Large Print, 2024)
A Christmas reunion: Tricia Troyer is thrilled when Brandt Massey, her cousin's English friend, joins the Troyers' holiday gathering for the second year in a row. The sparks between them are clear to everyone. When Brandt asks Tricia to be his girlfriend, they both know she'll have important choices to make about her future. But the two aren't as different as some believe--and with open hearts and understanding, their very own Christmas miracle just might be possible . . .